1988
DOI: 10.1002/anie.198809271
|View full text |Cite
|
Sign up to set email alerts
|

Silica‐Supported FePd Bimetallic Particles: Formation from Mixed‐Metal Clusters and Catalytic Activity

Abstract: Why are bi‐ and multimetallic heterogeneous catalysts more selective and stabler than their monometallic counterparts? Informative in this connection are AEM (analytical electron microscopy) investigations on catalysts which were prepared by thermal decomposition of the clusters 1 and 2 on SiO2 supports. The investigations indicate the presence of highly disperse bimetallic particles having the same metal ratio as the clusters. After the reaction the catalyst from the cluster 1 contains Pd particles (100–300 Å… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The average particle size of Pd alloys is nanometric (1-3 nm), indicating that the Zn(II) addition does not influence the particle size [123,132]. Nanometric (1-2 nm) and well dispersed PdFe clusters can be obtained also through the thermal decomposition method, as reported by Braunstein [208].…”
Section: Physico-chemical Characterizationsupporting
confidence: 54%
“…The average particle size of Pd alloys is nanometric (1-3 nm), indicating that the Zn(II) addition does not influence the particle size [123,132]. Nanometric (1-2 nm) and well dispersed PdFe clusters can be obtained also through the thermal decomposition method, as reported by Braunstein [208].…”
Section: Physico-chemical Characterizationsupporting
confidence: 54%
“…Braunstein et al. reported that extremely small PdFe clusters can be prepared by the decomposition of [FePd 2 (CO) 4 (dppm) 2 ] (dppm=1,1‐bis(diphenylphosphino)methane) or [Fe 2 Pd 2 (CO) 5 (NO) 2 (dppm) 2 ] on support SiO 2 29. Typical transmission electron microscopy (TEM) images are shown in Figure 1; the average particle size can be as small as 1–2 nm.…”
Section: Preparation Of Bimetallic Npsmentioning
confidence: 99%
“…A heterogeneous, bimetallic Fe-Pd complex catalyzes the carbonylation of 2-nitrophenol under 200 atm pressure of CO with high yields. [16,17] Additionally, the ruthenium-or palladium-catalyzed reductive carbonylation of o-nitrobenzylalcohols gives the corresponding 1,4-dihydro-2H-3,1-benzoxazin-2-one derivatives. [18] 2-Benzoxazolone can also be prepared in high yields by reductive carbonylation of 2-nitrophenol with a high pressure of carbon monoxide and a stoichiometric amount of sulfur or selenium in water in the presence of NEt 3 .…”
Section: Introductionmentioning
confidence: 99%